Prognostic Value of Elevated Cardiac Troponin I After Aneurysmal Subarachnoid Hemorrhage - Lin, Fa; Chen, Yu; He, Qiheng; Zeng, Chaofan; Zhang, Chaoqi; Chen, Xiaolin; Zhao, Yuanli; Wang, Shuo; Zhao, Jizong (Frontiers in Neurology, 2021)
Object: Patients with aneurysmal subarachnoid hemorrhage (aSAH) have an increased incidence of cardiac events and short-term unfavorable neurological outcomes during the acute phase of bleeding. We studied whether troponin I elevation after ictus can predict future major adverse cardiac events (MACEs) and long-term neurological outcomes after 2 years. Methods: Consecutive aSAH patients within 3 days of bleeding were eligible for review from a prospective observational cohort (ClinicalTrials.gov Identifier: NCT04785976). Potential predictors of future MACEs and unfavorable long-term neurological outcomes were calculated by Cox and logistic regression analyses. Additional Kaplan–Meier curves were performed. Results: A total of 213 patients were enrolled with an average follow-up duration of 34.3 months. Individuals were divided into two groups: elevated cTnI group and unelevated cTnI group. By the last available follow-up, 20 patients had died, with an overall all-cause mortality rate of 9.4% and an annual all-cause mortality rate of 3.8%. Patients with elevated cTnI had a significantly higher risk of future MACEs (10.6 vs. 2.1%, p = 0.024, and 95% CI: 1.256–23.875) and unfavorable neurological outcomes at discharge, 3-month, 1-, 2-years, and last follow-up (p = 0.001, p < 0.001, p = 0.001, p < 0.001, and p < 0.001, respectively). In the Cox analysis for future MACE, elevated cTnI was the only independent predictor (HR = 5.980; 95% CI: 1.428–25.407, and p = 0.014). In the multivariable logistic analysis for unfavorable neurological outcomes, peak cTnI was significant (OR = 2.951; 95% CI: 1.376–6.323; p = 0.005). Kaplan–Meier analysis indicated that the elevated cTnI was correlated with future MACE (log-rank test, p = 0.007) and subsequent death (log-rank test, p = 0.004). Conclusion: cTnI elevation after aSAH could predict future MACEs and unfavorable neurological outcomes.